Pore Type Inversion and S-Wave Velocity Estimation for the Characterization of Salawati Carbonate Reservoir - M. Syamsu Rosid; Yogi Muliandi; Al Hafeez (Geological Agency, 2021)
DOI: 10.17014/ijog.8.1.131-146A rock physic study was conducted in Salawati Basin, Papua, Indonesia. This field produces hydrocarbons from coral reef formation. The carbonate reservoir has a very heterogeneous and complex pore type. This study useddata from ten wells. Two wells (K-2 and Z-1) have Vs data, while the other eight do not. This study was done to identify the pore type of the reservoir rock, and to estimate the Vs log data in this area. The characterization of the carbonate reservoir was carried out using the DEM (Differential Effective Medium) inversion method. In calculating the bulk (κ) and shear (μ) modulus, the DEM method is supported by the HSW (Hashin-Shtrikman-Walpole) formula in the form of its rock matrix model and Gassmann's relation for its fluid contents. The inversion results show that in eight wells the reservoir is dominated by crack pore type, and in the other two wells the reservoir is dominated by stiff pore type. As for the Vs data, at reference wells K-2 and Z-1, the estimated Vs corresponds very well to the actual Vs, with RMS error of less than 2 m/s and 3 m/s respectively. Another qualitative verification shows that the pore type inversion results are almost perfectly consistent with thin-layer lithology data.